FAKTOR-FAKTOR YANG MEMENGARUHI PDB INDONESIA DENGAN PERSAMAAN SIMULTAN 2SLS - KUSUMAWARDHANI, NI MADE SRI; SRINADI, I GUSTI AYU MADE; SUSILAWATI, MADE (E-Jurnal Matematika; Volume 1, No 1, Tahun 2012DO - 10.24843/MTK.2012.v01.i01.p018, 2012)
Economic growth is indicated by an increase in the value of Gross Domestic Product (GDP). The size of GDP is influenced by various factors, including the Household Consumption, Investment, Government Spending, and Net Exports. One of the components that contribute to determine the amount of GDP is investment. According to the concept of macroeconomics, investment is also influenced by the GDP, tax revenue, and Currency. The reciprocal relationship between GDP and the investment is called a simultaneous relationship, therefore this study uses simultaneous equation Two Stage Least Squares (2SLS). 2SLS is one of the statistical methods used to replace the OLS method that can not be used to estimate an equation in a system of simultaneous equations. After analysis, the result shows the variables that influence the investment equation are GDP, tax , and revenue.
Keywords: 2SLS, GDP, Investment